Regularity of growth of fourier coefficients of entire functions of improved regular growth - Khats’, R. V.; Хаць, Р. В. (Institute of Mathematics, NAS of Ukraine, 2011)
We establish a criterion for the improved regular growth of entire functions of positive order with zeros on a finite system of half-lines in terms of their Fourier coefficients.